Biotechnology: A way to Control Environmental Pollution by Alternative Lubricants - Jain, Amit Kumar; Suhane, Amit (Research in Biotechnology, 2013)
Environmental concerns are gaining lot of interest due to increasing environmental pollution. Pollution is caused from various sources like fuel, lubricants, industrial waste, chemicals, noise etc. One of the major source of pollution is lubricant as it directly affect the environment when it is handled improperly, as lubricants from petroleum based oils have very poor biodegradability and also have high toxicity. Environmental pollution can be controlled by the use of biotechnology in the field of alternative lubricants from different available biomass. The current paper deals with the ways of reducing the environmental pollution by various alternative resources.